(3JYdjbGJ Ydi GdecGSHs - (3cGTa GdZWGA, eMeO QVG Hf gGOj Hf YHGS cGTa GdZWGA, J (B1366(3g` (B1947(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg adG Odjd dMQeI GdeYGedI EdG ef MjK GdJTQjY dG jbGd EPG cGfJ GdCOdI efUQaI Edi eG bUO (B... (3GdeMdd cGdTQH ddNeQ adG eYfi dJMQje GdeYGedIs
(3BNQgG (B:s
(3BNQgG(B: (3hgj eYjfI aj GdhGbY ajJQOO GdBNQ Hjf Cf jchf eJYdb Jdc GdeGdjI GdhGbYjI GdeMOhO GdeYjfI Ch eG jMJed chfg eKdG ajchf (B.. (3ef bHjd GdeJHGjjfs
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis